Projeto de filtros para atenuação de correntes de modo comum e de sobretensões em acionamentos de motores elétricos utilizando inversores PWM - Camila Cançado Flávio (2010)
The use of inverters in most of electrical motor drives applications has been accompanie by several undesirable effects, such as overvoltage at the motor terminals, circulation of common mode currents and electromagnetic interference problems. The determining factors for most of these problems come with the high switching speed and frequency ofthe semiconductor devices used in inverters. Another important factor is the long distance between the control centers and the place where the motors are installed, requering the use of long cables between the inverter and the motor, resulting in transmission line effects to the inverter output pulses. Such problems have been studied for about two decades, resulting in viable solution proposals. Methods that would mitigate problems related to overvoltage and common mode currents jointly became an interesting analysis proposal. Among the mitigation techniques, methodologies including dv/dt filters at the inverter output terminals and topologies to minimize the circulation of common mode currents were analyzed, once they configure typically methods employed in industrial facilities. In this scenario, a drive system simulation model was developed to represent all system elements that have direct influence on the problems in focus, in order to configure itself as a practical method for analyzing the differential mode and common mode phenomena and a comparison method for dv/dt filters and common mode topologies performance. The system model is developed in PSCAD/EMTDCc program for electromagnetic transients analysis, which is appropriate and very useful. Thus, the computational model developed in this work is presented as an additional option for methodologies development and optimization in filter design. Experimental analysis performed in the Laboratório de Aplicações Industriaisof theElectrical Engineering Departament of the Universidade Federal de Minas Gerais come along to validate the simulation system.